Adaptation and Validation of the “Dental Subscale of the Children's Fear Survey Schedule” (CFSS-DS) in the Ecuadorian population - Manzano Murillo, Andrea Cristina (2025)
Fear and anxiety toward the dentist are challenges that complicate clinical management, especially in children, and can interfere with the success of dental treatment. The aim of this study is to validate the "Dental Subscale of the Children’s Fear Survey Schedule" (CFSS-DS) for Ecuadorian children between the ages of 5 and 12 who were treated at the clinic of the Faculty of Dentistry of the Central University of Ecuador. An observational cross-sectional study was conducted with 147 participants. The CFSS-DS questionnaire, originally developed in English, was translated, adapted, and validated within the Ecuadorian context. The analysis was performed using SPSS v.27 software; internal consistency was assessed using Cronbach’s alpha (α > 0.75), and stability was measured with the Intraclass Correlation Coefficient (ICC = 0.95). Convergent and divergent validity were evaluated through Spearman’s correlation (rs = 0.57) and the Frankl scale, respectively. The proposed questionnaire (CFSS-DS-EC) demonstrated excellent psychometric properties and was confirmed to be a reliable and valid tool for measuring dental anxiety in Ecuadorian children.